1988
DOI: 10.1079/bjn19880099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of condensed tannins prepared from leaves of fodder plants on digestive enzymes in vitro and in the intestine of rats

Abstract: 1.Of the nineteen plants screened, six were found to contain large quantities of condensed tannins. Black locust (Robinia pseudo-dcucia), bush clover (Lespedezu bicolor), wistaria (Wistaria floribundu) and Japanese knotgrass (Reynoutria juponicu) were used for the present experiment. Tannins of the investigated plants were fractionated into three or four molecular forms, according to the degree of polymerization, by chromatography on a column of Sephadex LH-20.2. The protein-precipitating capacity of the fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(106 citation statements)
references
References 21 publications
5
100
0
1
Order By: Relevance
“…The BSA precipitation assay showed that there is a strong positive correlation between protein-binding capacity and procyanidin molecular weight, a finding that is in agreement with earlier studies (Kumar and Horigome, 1986;Horigome et al, 1988). Bioassays showed, however, that both the low and high molecular weight fractions were equally inhibitory to H. virescens larvae.…”
Section: Discussionsupporting
confidence: 81%
“…The BSA precipitation assay showed that there is a strong positive correlation between protein-binding capacity and procyanidin molecular weight, a finding that is in agreement with earlier studies (Kumar and Horigome, 1986;Horigome et al, 1988). Bioassays showed, however, that both the low and high molecular weight fractions were equally inhibitory to H. virescens larvae.…”
Section: Discussionsupporting
confidence: 81%
“…This deleterious effect is likely due to the reduction in the activities of trypsin and amylase in the digestive tract (Griffiths andMoseley, 1980;Horigome et al , 1988;Longstaff and McNab, 1991b). However, Griffiths and Moseley (1980) and Horigome et al (1988) observed that the activity of lipase increased in the digesta from the rats fed on a diet containing tannin-rich field bean hulls.…”
Section: Concentration the Evidence Gathmvd Fmm This Study Revealedmentioning
confidence: 97%
“…Legumes are inexpensive sources of proteins; however, they contain antinutritional factors such as tannins, phytates, and trypsin inhibitors, which if ingested can reduce the nutritional quality of the food and lead to undesirable physiological effects (14)(15)(16)(17). Therefore, they need to be processed prior to consumption to reduce the levels of these antinutritional factors.…”
Section: Introductionmentioning
confidence: 99%